V-V ECMO for severe Chlamydia psittaci pneumonia presenting with sudden cardiac arrest: A case report and literature review - Chen, Juan; Sun, Yong; Luo, Jian; Wu, Yang; Wang, Kaiyu; Zhang, Weiwen; Fang, Honglong (Medicine (Baltimore), 2024)
Rationale: Psittacosis, also known as parrot fever, is an infectious disease caused by Chlamydia psittaci, which can lead to C psittaci pneumonia. Clinical manifestations are highly nonspecific, which can vary from asymptomatic infection to severe pneumonia and even death. Patient concerns: In this case presentation, we reported one 65-year-old male case of C psittaci pneumonia who was admitted to our hospital on December 2, 2022 due to the chief complaints of poor appetite and fatigue for 3 days as the clinical manifestations. He denied contact with birds but admitted riding horses 1 week ago. Diagnoses: Chlamydia psittaci pneumonia of patient was confirmed through metagenomic sequencing of bronchoalveolar lavage fluid under bronchoscopy. Intervention: Patient was treated with V-V ECMO, invasive mechanical ventilation and CRRT. Outcomes: On December 12, the patient was successfully weaned off V-V ECMO and discharged on December 20, 2022. During postoperative follow-up, CT scan in a local hospital revealed the infiltrative lesions of the lung were absent. Lessons: This case prompts that metagenomic next-generation sequencing is a feasible diagnostic tool for psittacosis, which can rapidly worsen and even cause sudden cardiac arrest. V-V ECMO might be a viable emergency therapeutic option.